2020
DOI: 10.2174/1381612826666200716161610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effect of Metformin: A Molecular and Therapeutical Perspective

Abstract: : Aging is a time-dependent inevitable process, in which cellular homeostasis is affected, which has an impact on tissue function. This represents a risk factor for the development of numerous non-transmissible diseases. In consequence, the scientific community continues to search for therapeutic measures capable of improving quality of life and delaying cellular aging. At the center of this research is metformin, a widely used drug in Type 2 Diabetes Mellitus treatment that has a reduced adverse effects profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 149 publications
0
13
0
Order By: Relevance
“…Metformin, a rst-line drug for the clinical treatment of type 2 diabetes, is widely used in metabolic diseases due to its high effectiveness, safety and low cost. Increasing experimental and clinical studies have shown that metformin has multiple health bene ts in many disorders [11,19,29,36,42,43 ]. For instance, metformin was found to have anti-cancer, anti-aging and anti-oxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin, a rst-line drug for the clinical treatment of type 2 diabetes, is widely used in metabolic diseases due to its high effectiveness, safety and low cost. Increasing experimental and clinical studies have shown that metformin has multiple health bene ts in many disorders [11,19,29,36,42,43 ]. For instance, metformin was found to have anti-cancer, anti-aging and anti-oxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nobel prize winner Dr. Rita Levi-Montalcini, who discovered the NGF, applied NGF in the form of eye drops for the rest of her life and lived 103 years [171]. Although the role of NGF in significantly prolonging life expectancy has not been clearly demonstrated, some studies have shown its effect on the suspension of certain senile diseases and prolongation of the functioning of vital body systems [12,42,122,167,[172][173][174][175]. Decreased NGF levels are associated with cognitive decline and Alzheimer's disease.…”
Section: Ngf and Neural Regenerationmentioning
confidence: 99%
“…Blocking factors that negatively affect lifespan is a reasonable strategy to prevent early disability and prolong the active life of older people. Among such strategies, tested in the clinical practice or which will be translated to the clinical practice, one can highlight overcoming the insulin resistance by diet restriction [8], increasing FGF21 in blood circulation, pharmacological treatment of insulin resistance (e.g., with dehydroepiandrosterone and metformin) [12,14], stimulation of tissue repair by GH, oxytocin, GDF11 and TIMP2 [203], vascular regeneration with bFGF, EGF, VEGF, PDGF-AB, and BMP9, preventing the development of "inflammaging" by administering anti-inflammatory molecules, including COX-2 inhibitors, leukotriene receptor antagonists, TIMP2, or other matrix metalloproteinase inhibitors [210,263], overcoming the cell senescence by administration of TM5441 analogs, optimizing the autophagy and mitophagy with mTOR inhibitors (rapamycin analogs) [264], with TGF-β inhibitors [110,264], antioxidant therapy [265,266], reduction of NAD+ exhaustion [73]. The indicators and mechanisms discussed above reflect the natural and pathological aging processes.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to treating diabetes, metformin also plays an essential role in the treatment of other diseases, such as anticancer [ 7 ], antiaging [ 8 , 9 ], treatment of gestational hypertension [ 10 ] and hypertension [ 11 ], and weight loss [ 12 ]. In addition, metformin use could reduce the risk of hypertension [ 13 ] and stroke [ 14 ].…”
Section: Introductionmentioning
confidence: 99%